2000
DOI: 10.2337/diabetes.49.4.633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of troglitazone on blood concentrations of plasminogen activator inhibitor 1 in patients with type 2 diabetes and in lean and obese normal subjects.

Abstract: Low plasma fibrinolytic activity in association with increased plasma plasminogen activator inhibitor 1 ( PAI-1) levels has been linked to an increased risk of atherosclerosis in obesity and type 2 diabetes. We tested the hypothesis that troglitazone, which improves insulin sensitivity and lowers plasma insulin levels in insulin-resistant obese subjects and patients with t y p e 2 diabetes, would also lower circulating PA I -1 antigen concentrations and activity. We assessed insulin sensitivity (5-h, 80 mU · m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(108 citation statements)
references
References 28 publications
3
102
0
3
Order By: Relevance
“…Clinical studies have found increased levels of E-selectin, ICAM-1 and VCAM-1 in patients with diabetes, and higher levels were associated with a subsequent risk for cardiovascular events [16,27,28]. Similarly, high concentrations of PAI-1 and subsequent downregulation of fibrinolysis have been implicated in the increasing morbidity, mortality and risks for thrombotic disease in diabetic patients [18,19]. VEGF and sFLT-1 may also play a role in the pathophysiology of atherosclerosis by initiating and propagating angiogenesis, and thereby providing a passage for inflammatory cells to the site of injury [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have found increased levels of E-selectin, ICAM-1 and VCAM-1 in patients with diabetes, and higher levels were associated with a subsequent risk for cardiovascular events [16,27,28]. Similarly, high concentrations of PAI-1 and subsequent downregulation of fibrinolysis have been implicated in the increasing morbidity, mortality and risks for thrombotic disease in diabetic patients [18,19]. VEGF and sFLT-1 may also play a role in the pathophysiology of atherosclerosis by initiating and propagating angiogenesis, and thereby providing a passage for inflammatory cells to the site of injury [29].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have demonstrated increased levels of the adhesion markers E-selectin, ICAM-1 and VCAM-1 in patients with diabetes [15][16][17]. Increased levels of PAI-1 have also been found in patients with diabetes, increasing their risk for thrombotic disease [18,19]. Interestingly, these elevated levels of circulating markers are thought to play a role in the accelerated development of atherosclerotic plaques in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of PPARg by thiazolidinediones has been shown to have a range of beneficial vascular effects, including vasorelaxation via blockade of K + channels 7 and reduction of voltage-gated Ca 2+ current, 8 inhibition of the proliferation and migration of vascular smooth muscle cells, 9,10 inhibition of angiogenesis, 11 and improvement in markers of inflammation and fibrinolysis. [12][13][14] These observations indicate a potential for thiazolidinediones to modify risk of vascular complications in diabetes.…”
Section: Introductionmentioning
confidence: 87%
“…Lipid lowering agents, pharmacologic inhibition of the RAS [161], improvement of insulin sensitivity and glucose metabolism [187,188] can reduce raised PAI-1 and enhance impaired fibrinolysis. Treatment with ACEI is associated with reductions in PAI-1 levels and a lower incidence of ischemic CV events [189].…”
Section: Strategies To Improve Fibrinolytic Capacitymentioning
confidence: 99%